PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU - Aria, Ririn Restu (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
New admissions is an essential part of the school to be recognized or selected by parents in order to enroll their children at the school. Various ways of promotion every year is always done to make it more known by parents and prospective students themselves in choosing schools that match their interests and skills possessed by prospective students in the school department contained. Originally a school just introduced their schools offline either using banners or promotions of students who are already attending the school without the help of technology that can be used by parents, but the use of the internet is now enabling everyone to be able to search for information quickly and efficiently without wasting time in getting the desired information, that's what made the design of new admissions online. In this system all of which related to the procedures of registration, majors available, fees based on the subject as well as the orientation of learners can be determined directly by parents and prospective students who will enroll at the school. Prospective students can also provide information relating to personal order to complete the personal details of prospective students before the new admissions process is done so that the data - the data provided can be used for new admissions process to the next stage. While using the website easier for administrators to manage data related to prospective students and to update the information relating to schools ranging from registration procedure, facility, fees and registration statements relating to new admissions. By using the internet and website are expected to facilitate the prospective student registration, more efficient and more affordable to the general public Keyword : System design, enrollment, website